2006
DOI: 10.1038/sj.cdd.4401996
|View full text |Cite
|
Sign up to set email alerts
|

Eriocalyxin B induces apoptosis of t(8;21) leukemia cells through NF-κB and MAPK signaling pathways and triggers degradation of AML1-ETO oncoprotein in a caspase-3-dependent manner

Abstract: Diterpenoids isolated from Labiatae family herbs have strong antitumor activities with low toxicity. In this study, Eriocalyxin B (EriB), a diterpenoid extracted from Isodon eriocalyx, was tested on human leukemia/lymphoma cells and murine leukemia models. Acute myeloid leukemia cell line Kasumi-1 was most sensitive to EriB. Significant apoptosis was observed, concomitant with Bcl-2/Bcl-X L downregulation, mitochondrial instability and caspase-3 activation. AML1-ETO oncoprotein was degraded in parallel to casp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
79
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(86 citation statements)
references
References 39 publications
(42 reference statements)
7
79
0
Order By: Relevance
“…Concurrently with apoptosis, AML1/ETO protein degradation was also induced in Kasumi-1 cells treated with 0.1 mM ITF2357. We demonstrated that this degradation was determined by caspase activation, well in keeping with what recently observed in Kasumi-1 cells exposed to diterpenoids (Wang et al, 2007).…”
Section: Selectivity Of Low-dose Itf2357 In Aml Subtypes V Barbetti Esupporting
confidence: 90%
“…Concurrently with apoptosis, AML1/ETO protein degradation was also induced in Kasumi-1 cells treated with 0.1 mM ITF2357. We demonstrated that this degradation was determined by caspase activation, well in keeping with what recently observed in Kasumi-1 cells exposed to diterpenoids (Wang et al, 2007).…”
Section: Selectivity Of Low-dose Itf2357 In Aml Subtypes V Barbetti Esupporting
confidence: 90%
“…More recently, Chen and coworkers also reported that the degradation of AML1-ETO oncoprotein was paralleled to caspase-3 activation in apoptotic Kasumi-1 cells induced by eriocalyxin B and oridonin. 17,18 Based on these discoveries, we further used an in vitro system to identify potential cleavage sites in AML1-ETO with human recombinant active caspase-3. The results revealed that the recombinant active caspase-3 was able to cleave both immunoprecipitated FLAG-AML1-ETO and bacterially expressed GST-AML1-ETO protein into one or two fragments, which also existed in ex vivo system and was blocked by caspase-3 inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…17 Recently, AML1-ETO protein was also shown to be degraded in apoptosis induced by eriocalyxin B and oridonin. 17,18 In addition, apoptosis-independent degradation of AML1-ETO was also reported. 19 The exact mechanisms and biological significance of AML1-ETO degradation remain to be further explored.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the cells become round-shaped and poorly adhered to the cultured plates while the control group cells showed a typical polygonal and cobblestone monolayer appearance and remained firmly attached to cultured plates (data not shown). The results indicated that EriB induced growth inhibition of T24 cells, in addition to other type of cancer cells previously reported including ovarian cancer (Leizer et al, 2010), pancreatic adenocarcinoma (Li et al, 2012) and leukemia (Wang et al, 2007;Zhang et al, 2010). …”
Section: Resultsmentioning
confidence: 63%
“…Eriocalyxin B (EriB) is a natural entkaurene diterpene compound isolated from Isodon eriocalyx var. laxiflora, a herb of the Labiatae family distributed in the South-West China and has been reported to have wide spectrum of biological effects, including anti-inflammatory and antibacterial agent in local folk medicine (Ikezoe et al, 2003;Wang et al, 2007). Furthermore, EriB has anti-proliferative effect and induced apoptosis in cancer cells such as ovarian cancer (Leizer et al, 2010), pancreatic adenocarcinoma (Li et al, 2012) and leukemia (Wang et al, 2007;Zhang et al, 2010).…”
mentioning
confidence: 99%